The Impact of Supply Chain Resilience on Supply Chain Performance under the Moderating Effect of Sustainability: A Study under The Chinese Business Context - Li, Jiahao (2022)
In the context of economic globalization, when faced with a series of unpredictable risks, such as political unrest between countries, pandemics, war, and natural disasters, the vulnerability of the enterprise supply chain is prominent, and more and more enterprises begin to attach importance to sustainable development. These factors put higher demands on supply chain resilience (SCRE), affecting supply chain performance (SCP). This study aims to explore the impact of corporate SCRE on SCP under the mediating role of SC sustainability. Through literature review, the sub-dimensions of each variable are determined, and the questionnaire collection and empirical analysis are conducted on 159 enterprises distributed in 14 industries. The results show that SCRE has a positive and significant impact on SC sustainability, SCRE has a direct positive impact on SCP, and SCRE has an indirect positive impact on SCP under the mediating effect of SC sustainability. The study also introduces a representative Chinese enterprise as a case study, combines theory with practice, and proposes a series of implications for strengthening SCRE in management. The limitations of this study are that the sample size is relatively small, and the results are time-sensitive and may not be universal. In addition, the results obtained in the case analysis section may also be affected by the subjective factors of the researchers.